The ruby knight - Eddings, David (Eddings, David. Elenium, 1991)
Sparhawk, Knight and Queen's Champion, and his companions brave untold perils as they seek the Bhelliom, a fabulous, long-lost jewel with the power to cure the poison that threatens the life of Ehlana, Queen of Elenia.